THE EFFECT OF PRICE AND PRODUCT QUALITY ON FERTILIZER PURCHASES AT AM JAYA TANI (Solokan Jeruk District, Bandung Regency) - Vina Sri Wulan; Wentri Merdiani (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the effect of price and product quality on fertilizer purchases at Am Jaya Tani Store in Rancakasumba Village, Solokan Jeruk District, Bandung Regency. This research is motivated by a decline in the number of visitors and fertilizer purchases, which is presumed to be influenced by consumers’ perceptions of price and product quality. The research method used is a quantitative approach with descriptive and verificative analysis. Data were collected through questionnaires distributed to consumers of Am Jaya Tani Store, with sampling determined based on specific criteria. The data analysis techniques include validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing using partial (t-test) and simultaneous (F-test) methods. The results indicate that descriptively, price, product quality, and fertilizer purchases are in the fairly good to good category. Partially, price has a significant effect on fertilizer purchases, and product quality also has a significant effect on fertilizer purchases. Simultaneously, price and product quality have a significant effect on fertilizer purchases at Am Jaya Tani Store. The findings of this study are expected to provide practical insights for the management of Am Jaya Tani Store in formulating pricing strategies and improving product quality to increase fertilizer purchases and enhance business competitiveness.